Cause-Related Marketing Communications in the Indian Context: A Historical Research (International Journal of Food and Nutritional Sciences, 2022)
Cause-related marketing (CRM) has emerged as a prominent strategy employed by companies worldwide to enhance their brand image and engage consumers by aligning with social causes. While extensive research on CRM exists in a global context, there is a paucity of studies that specifically explore its historical development and impact in the Indian market. This historical research analysis aims to fill this gap by examining the evolution of cause-related marketing communications in the Indian context.